Effects of natural and synthetic fibers in turfgrass horse racing surfaces as characterized by triaxial shear tests - Schmitt, P.; Erbland, P.; Peterson, M. L. (Sports Engineering, 2025)
Soils used in putting green applications are designed to move water quickly through the profile yet are still able to support turfgrass growth. North American turfgrass horse racing surfaces often use similar soils which are reinforced with synthetic fibers to achieve both high infiltration rates and high shear strength. Natural fibers, in particular jute and sisal, are a promising and more environmentally benign method of increasing the shear strength of soils. The purpose of this study was to submit unreinforced and reinforced golf course soil with synthetic and natural fibers to triaxial shear testing for potential use in Thoroughbred racetracks. Laser diffraction particle size analysis was used to characterize the texture. Bulk density testing was used to determine the moisture content at which peak bulk density occurs. Triaxial shear analysis was then conducted on the soil with the three different types of reinforcement at a moisture content above and below the peak bulk density value. Synthetic fiber reinforcement produced a 10% increase in friction angle and nearly a 50% reduction in cohesion. Both are beneficial improvements for the turfgrass Thoroughbred racing application. Natural fibers produced a comparable change in both friction and cohesion although moisture has an inverse relationship to friction angle. Natural fibers appear to be well suited for divot repair mixes and newly established turf courses. Future research is needed to understand the life span of natural fibers in the soil profile as well as their impact on surface hardness.